Women in the Russian penal system: the role of distance in the theory and practice of imprisonment in Russia - Pallot, Judith (UK Data Service, 2015)
This project aimed to explore how the isolation that women in Russia's penal institutions suffer shapes their experiences of custody and re-entry into society. 65 prisoners, 21 ex-prisoners, 30 prison personnel, and 71 local inhabitants of penal regions were interviewed, forming 186 semi-structured, face-to-face interview transcripts. Another 300 prisoners completed self-completion questions between 2007 and 2009. At the end of 2004, there were approximately 36,000 women imprisoned in 40 of Russia's penal colonies.The majority were held at considerable distances from home, often in remote places difficult for their relatives to access. The negative influence of distance on prisoners - its contribution to high rates of recidivism and poor prisoner mental and physical health - is recognised by the post-Soviet authorities. In reforms to the 'correctional code', Russia has pledged itself to holding prisoners near to home, but women are excluded from this provision. The research will examine how the isolation suffered by women in Russia's penal system shapes their experiences of custody and the decisions they make at the end of their sentences. The project is the first systematic study of the geography of imprisonment in Russia. It will involve first-hand research in penal colonies in three regions and will employ both quantitative and qualitative methods. In addition to women prisoners, the researchers will conduct interviews with prison officers, other members of the penal service and voluntary organisations. The results will be analysed in the context of the continuities and changes in Russia's broader penal geography in the past two decades.